Unemployment is associated with lower cortisol awakening and blunted dehydroepiandrosterone responses. (July 2016) - Gallagher, Stephen; Sumner, Rachel C.; Muldoon, Orla T.; Creaven, Ann-Marie; Hannigan, Ailish
Highlights: Unemployment is thought to influence health via stress-induced HPA activation. Unemployed people have a lower cortisol awakening response. Unexpectedly, unemployment is associated with lower cortisol:DHEAS ratio. First identification of blunted DHEAS response to stress of unemployment. Abstract: Previous research has investigated the endocrinological consequences of unemployment as a likely pathway behind chronic stress and negative health outcomes. Despite these early attempts at delineating the neuroendocrine consequences of the chronic stress experienced by the unemployed, identifying a consistent and stable effect has remained elusive. Here we sought to strengthen existing knowledge into the effect of the stress of employment status on cortisol by improving on the methodological weaknesses of earlier studies and extend this line of enquiry by measuring the steroid hormone Dehydroepiandrosterone-Sulfate (DHEAS). Saliva samples were collected from unemployed and employed participants at four time points across two days. As expected, unemployed people reported higher stress, lower social support and lower self-esteem. Unexpectedly, the unemployed showed lower overall cortisol output, a likely consequence of a higher cortisol awakening response (CAR) in the employed. However, they also had a higher DHEA output across the day, albeit the diurnal pattern across the day was more dysregulated compared to that seen in those employed with a blunted response evident in the evening; the cortisol:DHEAS ratio was also lower in the unemployed group. Further, these hormone differences were correlated with self-esteem and stress. Taken together these results suggest that the relationship between employment status and endocrine responses is far more complicated than previously thought. We have shown for the first time that unemployed people have a lower CAR, but also show a blunted DHEA response relative to those employed and we suggest that this may be a feature of chronic stress exposure or perhaps dependent on the prevailing socio-economic context.